Sensitivity of a Preclinical Alzheimer's Cognitive Composite (PACC) to amyloid β load in preclinical Alzheimer's disease. Issue 6 (3rd July 2019) - Bransby, Lisa; Lim, Yen Ying; Ames, David; Fowler, Christopher; Roberston, Joanne; Harrington, Karra; Snyder, Peter J.; Villemagne, Victor L.; Salvado, Olivier; Masters, Colin L.; Maruff, Paul
ABSTRACT: Introduction : Preclinical Alzheimer's disease (AD) is characterized by amyloid-related cognitive decline. Reduction in this decline is used to determine the efficacy of drug therapies designed to forestall the disease in preclinical AD clinical trials, measured by a Preclinical Alzheimer's Cognitive Composite (PACC). Most studies estimate rates of cognitive change by comparing cognitively normal (CN) older adults with abnormally high beta-amyloid (Aβ+) to those with low levels (Aβ–). However, participants of preclinical AD clinical trials must be Aβ+ for entry. Therefore, we estimated the effect of very high amyloid (Aβ++) and Aβ+ on cognitive change over three years measured by different versions of the PACC in individuals with preclinical AD. Method : CN older adults underwent Aβ neuroimaging and neuropsychological assessments over three years as part of the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. Three cognitive composite scores were computed: the Alzheimer's Disease Cooperative Study (ADCS)–PACC, the ADCS–PACC with no Mini-Mental State Examination (MMSE), and the z -scores of Attention, Verbal Fluency and Episodic Memory for Nondemented Older Adults (ZAVEN) composite. Results : Compared to the Aβ++ group, the Aβ+ group showed a slower rate of cognitive decline with the largest magnitude of difference reflected by the ADCS–PACC ( d = 0.85). The ADCS–PACC excluding the MMSE and the ZAVEN also reflected a moderate to large magnitude of difference between groups ( d = 0.62, d = 0.72, respectively). Conclusions : When all individuals have abnormal Aβ, the level of Aβ at baseline is associated with the rate of subsequent decline. The ADCS–PACC was the most sensitive composite score in showing that lower Aβ is associated with a slower rate of cognitive decline; however, there are limitations to the use of the MMSE. These results provide a benchmark of comparison for preclinical AD clinical trials aiming to slow cognitive deterioration.